Growing global: How to manage people globally and locally. Issue 45 (March 2014) - Fowler, Andrew
Abstract : Over the past two decades, globalisation, innovation and rapid advances in technology have helped businesses to expand into new territories, grow their customer bases and significantly increase sales.